Teacher–Parent Collaboration in Fostering Islamic Character Development among Junior High School Students - Stepi Andini Putri; Rina Juliana (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study examines the collaboration between Islamic Religious Education (PAI) teachers and parents in fostering students' Islamic character at SMP Negeri 17 Tanjung Jabung Timur, a topic of growing importance amid the moral challenges facing Indonesian adolescents in the digital era. The purpose of this research is to describe the forms of collaboration between PAI teachers and parents, and to identify the supporting and inhibiting factors involved. This topic is significant because character formation cannot rely solely on school-based instruction but requires consistent reinforcement at home. This study employed a qualitative descriptive approach, with data collected through observation, semi-structured interviews, and documentation, involving PAI teachers, students, parents, and the school principal as informants. The findings reveal that collaboration is implemented through structured religious habituation programs at school, the use of the